Judaism for gentiles reading Paul beyond the parting of the ways paradigm - Runesson, Anders 1968-; Runesson, Rebecca 1995-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
Cover -- Title -- Table of Contents -- Prologue -- Part I: Approaching Paul -- 1. Understanding Paul as a First-Century Jew in the Twenty-First Century: The Problem of Relevance, Bias, and Approach -- 1.1 The Nature of the Text and the Search for a Persuasive Paul -- 1.2 History and Its Usefulness: Paul Within and Beyond Christianity -- 1.3 Paul Within Judaism: The Issue of Collective Bias -- 1.4 Excavating Paul: Beyond the Parting of the Ways Paradigm -- 2. Particularistic Judaism and Universalistic Christianity? Critical Remarks on Terminology and Theology -- 2.1 Terminology and Theological Pitfalls -- 2.2 The Terms "Universalism" and "Particularism" in Current Usage -- 2.3 More Precise Terminology: A Suggestion -- 2.4 The New Terminology in Use -- 2.5 Beyond the Universal and the Particular -- 3. Was there a Christian Mission Before the Fourth Century CE? Problematizing Common Ideas About Early Christianity -- 3.1 Jewish Mission Then and Now -- 3.2 Mapping the Area - Initial Steps -- 3.3 Changing the Facts on the Ground: The Creation of "Religion" (and "Christianity") -- 3.4 Pre-Christian Mission Beyond "Religion" -- 3.4.1 Defining "Mission" -- 3.4.2 Outlining Parameters and a Mode of Procedure -- 3.5 The Private Sphere: The Role of the House in Spreading a Cult -- 3.6 The Dynamic Space In-Between: Associations and Mysteries -- 3.7 Claiming the World: Colonialism as Theo-Political Pattern for Proselytizing Mission -- 3.7.1 Conquest and Mission -- 3.7.2 Restoration and Counter-Colonialism: The Margins Strike Back -- 3.8 From Jerusalem to Rome - A One Way Ticket? -- 4. Entering the Conversation on Paul: Was he a Christian and did he Attend Church? -- 4.1 Terminology as Translation -- 4.2 Translating History: Colonizing the Past or Liberating the Dead? -- 4.3 Changing the Architecture of the Conversation -- 4.4 "Christians"/"Christianity".
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung